An Atypical Parvovirus Drives Chronic Tubulointerstitial Nephropathy and Kidney Fibrosis - Roediger, Ben; Lee, Quintin; Tikoo, Shweta; Cobbin, Joanna C.A.; Henderson, James M.; Jormakka, Mika; O’Rourke, Matthew B.; Padula, Matthew P.; Pinello, Natalia; Henry, Marisa; Wynne, Maria; Santagostino, Sara F.; et al. (Cell, 2018)
The occurrence of a spontaneous nephropathy with intranuclear inclusions in laboratory mice has puzzled pathologists for over 4 decades, because its etiology remains elusive. The condition is more severe in immunodeficient animals, suggesting an infectious cause. Using metagenomics, we identify the causative agent as an atypical virus, termed “mouse kidney parvovirus” (MKPV), belonging to a divergent genus of Parvoviridae. MKPV was identified in animal facilities in Australia and North America, is transmitted via a fecal-oral or urinary-oral route, and is controlled by the adaptive immune system. Detailed analysis of the clinical course and histopathological features demonstrated a stepwise progression of pathology ranging from sporadic tubular inclusions to tubular degeneration and interstitial fibrosis and culminating in renal failure. In summary, we identify a widely distributed pathogen in laboratory mice and establish MKPV-induced nephropathy as a new tool for elucidating mechanisms of tubulointerstitial fibrosis that shares molecular features with chronic kidney disease in humans. [Display omitted] •Inclusion body nephropathy is caused by mouse kidney parvovirus (MKPV)•MKPV is widely distributed in animal facilities in Australia and North America•MKPV is highly divergent from other mouse parvoviruses•Uncontrolled MKPV infection in immunocompromised mice results in renal failure A kidney parvovirus found in multiple laboratory mouse colonies causes spontaneous nephropathy and represents a new tool for studying chronic kidney disease.